Gry komputerowe jako narzędzie resocjalizacji – wprowadzenie do problematyki i perspektywy badawcze - Łukasiak, Anna (Kultura-Społeczeństwo-Edukacja, 2023)
The aim of the article is to present computer games as a potential tool for application in social rehabilitation. The author extensively discusses fundamental issues related to computer games, such as terminology and definitions, while focusing on highlighting their distinctive features and diverse functions. Additionally, the article provides social and scientific justification for conducting research on the discussed topic, emphasizing the significance of computer games as a socio-cultural medium, the ongoing phenomenon of digitization, and the increasing engagement of users in such activities. To establish the theoretical foundations, the article refers to contemporary theories of resocialization, including social interactionism theory, creative resocialization, the concept of resilience, and cognitive theories. Furthermore, the author reviews the Polish scientific discourse on games in the field of social rehabilitation pedagogy, highlighting the lack of publications and studies regarding the utilization of computer games in this context. The conducted analysis indicates that the issue of employing computer games in resocialization remains undescribed and unexplored in domestic literature, which may serve as motivation for further research in this field in the future. The discovery of the potential that computer games have in the resocialization process can contribute to their utilization as an effective supporting tool for this process, bringing tangible benefits to individuals at risk of social maladjustment or social non-adaptation. Modernizing the process of resocialization through the use of computer games allows for the creation of an interactive and engaging environment that promotes active learning, the development of social skills, and the cultivation of prosocial attitudes. With their interactivity and adaptability to individual needs, computer games can provide a more efficient and personalized approach to resocialization, thus facilitating a better process of social reintegration for individuals.